PENINGKATAN PENGETAHUAN GIZI DAN PENDAMPINGAN BALITA BAWAH GARIS MERAH (BGM) DAN STUNTING DI WILAYAH KERJA PUSKESMAS BALONGPANGGANG KABUPATEN GRESIK - Mas'udatus Saniyah; Titik Asmaiyah; Dwi Faqihatus Syarifah Has (Ghidza Media Jurnal, 2021)
Toddlers with body weight under the red line (BGM) and stunting indicate malnutrition. The purpose of this study is to assist toddlers who are malnourished and stunted by means of education and nutrition counseling. This research method is a cross sectional and experimental study. The research was conducted in two stages, namely the collection of basic data and then intervention according to the causes of the problems found. Total of 21 BGM and stunting toddlers were assigned as research subjects. Sampling was done by non-probability sampling method. The results showed that after carrying out nutritional education, the knowledge of mothers under five increased and was more familiar with innovations in nutrient-dense food products. The results of nutritional counseling monitoring related to weight and height showed a significant increase (p<0.05), while monitoring food intake showed an insignificant value (p>0.05). So it can be concluded that educational and counseling interventions can potentially overcome the problem of under-fives with malnutrition and stunting.